CREATING KNOWLEDGE-BASED SOCIETY AND KNOWLEDGE ECONOMY: THE MAIN PRINCIPLES AND PHENOMENA - Melnikas, Borisas (Ekonomika, 2010)
Theoretical problems and priorities of the scientific research on creating knowledge-based society and knowledge economy are described and analyzed in the article. A new concept of knowledge-based society and knowledge economy creation and development processes is described. The main idea is that knowledge-based society and knowledge economy creation and development processes may be attributed to the category of global transformation processes, therefore, all general phenomena and characteristics of global transformations are absolutely typical of the creation and development of knowledge-based society and knowledge economy. The processes of creating knowledge-based society and knowledge economy are analyzed in the general context of global transformations processes. The main principles of creating knowledge-based society and knowledge economy, as well as the main phenomena of knowledge-based society and knowledge economy creation processes are described. Creating and modernizing knowledge-based society and knowledge economy are very complicated processes oriented to the formation of a new quality of society and a qualitatively new lifestyle. These processes may be described as especially complicated, because they pursuie a new quality in two aspects: • knowledge-based society and knowledge economy, compared to “traditional” society and economy, are in all cases described as qualitatively new; • creation and development of knowledge-based society and knowledge economy take place under conditions of global changes, which means that qualitative changes take place in all global space, the essence of those changes being creation and spread of knowledge-based society and knowledge economy. The universal principle of the “new quality creation” is characterized. This principle shows that new quality always forms itself or is formed on the ground of conjugation when elements of different origin, which have never before belonged to the same system, merge into a common interaction system, and that the conjugation processes may be of two types–those of integration and synthesis. The general and some specific phenomena of creating knowledge-based society and knowledge economy are characterized.